Penurunan Jumlah Lahan Dan Perubahan Budidaya Tanaman Kopi Bali Kintamani Mengancam Destinasi Wisata Kopi Di Kintamani - Permana, Ijlal Faiz Bayu; Sukana, Made (JURNAL DESTINASI PARIWISATA, 2019)
This research is conducted in Catur Village, Kintamani District, Bangli Regency. The purpose of this research is to identify the decreasing number of coffee land of Kintamani Bali Coffee plantation and its causes. The data used in this research are qualitative and quantitative, while the data of this research consists of of primary and secondary data. The data is collected through observation, depth interviews, and documentation. The informants are determined through purposive sampling procedure, and they are I Ketut Jati (Head of Masyarakat Perlindungan Indikasi Geografis Kintamani) and Kocong Neca (Local Coffee Farmer). Afterward, the data that has been found is analyzed by descriptive qualitative method. The results of this research show that the decreasing number of coffee land of Kintamani Bali Coffee plantation on has reach its dangerous point and threaten tourism in Kintamani. In the last two years, the number of coffee land of Kintamani Bali Coffee had decreased significantly from 6.335 Ha to 4.772 Ha and automatically causing the total production of Kintamani Bali Coffee beans dropped from 2.314 Ton to 2.046 Ton. The biggest reason of the decreasing number of coffee land came from land conversion. The difference of income between coffee plantation with orange plantation also made farmers in Desa Catur to shift to grow more orange than coffee. In a 0,5 Ha field, orange plantation could gain profits approximately for Rp 114.945.000, while coffee plantation only gain profits for Rp 63.530.000. Moreover, plant-paracitic nematodes are damaging the coffee plantation. Therefore, the number of lands to grow coffee are decreasing. The recomendation from this research addressed to government service of Agriculture, Plantation and Forestry Bangli to keep oversee Kintamani Bali Coffee plantation and give an aid towards the Nematoda Parasite Diseases problem. Furthermore, farmers required to improve their human resource’s skill, so they can use management system on their plantation. Keywords: Land Degradation of Plantation, Change of Plant Cultivation, Kintamani Bali Coffee, Coffee Tourist Destination, Kintamani District